Opening the 'Black Box' of Cooperative Learning in Face-to-Face versus Computer-Supported Learning in the Time of COVID-19 - Shu Yu; Takaya Yuizono (MDPI AG, 2021)
This paper aims to identify the changes in student behaviors that resulted from the switch from face-to-face (F2F) learning to computer-supported cooperative learning (CSCL) due to the coronavirus (COVID-19) pandemic. We constructed a triple-dimensional index with "thinking ability improvement", "horizontal knowledge construction", and "vertical social relationship evolution" to make comparisons. According to majors, we selected 23 students who registered for entrepreneurship courses from March to June 2019 in F2F and 23 students from March to June 2020 in CSCL formats. We utilized mixed methods, including experimental, content-based, and social network methods, to conduct evaluations. The results show the following: (1) Cooperative learning is beneficial in cultivating creative thinking for both F2F and CSCL groups. (2) The level of knowledge construction was slightly higher in F2F than that in CSCL in general. The effect of F2F learning in the early stage of the course was better, and in the later stage of the class CSCL attained a higher value. (3) For social abilities, the interactions in CSCL were closer than those in the F2F group. F2F cooperative learning was more prone to "fake cooperation" and free-riding behavior, whereas CSCL led to "pan-cooperation" and lacked the in-depth exploration of knowledge. Therefore, this pandemic provides opportunities for cooperative learning with in-depth exploration. CSCL offers sustainable and more hybrid learning activities that allow for the combination of online and offline learning to be experienced according to course contents.